Determination of carnosic acid and carnosol in Rosmarinus officinalis L. by high-performance capillary electrophoresis. Issue 3 (4th May 2017) - Lu, Ping; Ma, Jin-qi; Li, Pu; Zhou, Hai-mei; Xu, Xing-min; Guo, Wan
ABSTRACT: Carnosol and carnosic acid in Rosmarinus officinalis L. were separated by high-performance capillary electrophoresis using a 50 cm capillary, a 12 mmol/L 80:20 pH 9.9 borax:methanol buffer using 25 kV of applied voltage at 30°C with detection at 280 nm. Rosmarinus officinalis L. was extracted with methanol with ultrasound at 170 W and 50 kHz for 20 min. The precision, repeatability, and recovery of the method were evaluated. The calibration relationships for carnosol and carnosic acid were y = 2.331x + 5.92 from 0.01 to 0.160 mg/mL and y = 7.980x + 4.32 from 0.005 to 0.080 mg/mL, respectively. The established method allows the separation and quantification of carnosic acid and carnosol in R. officinalis from various locations in China.